Carnet de Route d’un voyageur Congolais: Masala à l'exposition universelle d’anvers, en 1885 - première partie - - Etambala, Zana Aziza (Afrika Focus, 1993)
Masala, the central figure in this article, came to Belgium to be exhibited, together with eleven other natives of the Congo Independent State, at the International Fancy Fair organized in Antwerp in 1885. Of course, the illiterate Masala didn't take notes during his stay in Antwerp. But a meticulous investigation of the contemporary local press, which paid enough attention to this event, made it possible to describe in detail the daily european experiences of Masala and his companions. It also enables us to examine the 'white ' belgian view on the black subjects of Leopold II. KEYWORDS: Exhibition of Congolese, World Exhibition of Antwerp (1885)